Analysing the effectiveness of topical bleeding care following tooth extraction in patients receiving dual antiplatelet therapy-retrospective observational study - Bogumił Lewandowski; Aleksander Myszka; Małgorzata Migut; Ewelina Czenczek-Lewandowska; Robert Brodowski (BMC, 2021)
Abstract Background Patients using antiplatelet drugs following infarctions, acute coronary syndrome or stroke pose a significant clinical problem if it is necessary to perform surgery, including dental surgery, since they are at risk of prolonged or secondary post-extraction bleeding. Discontinuation of this therapy is associated with a high risk of serious thromboembolic complications. The purpose of this study was to assess the effectiveness of TachoSil fibrin-collagen patches in stopping and preventing of secondary post-extraction bleeding in patients undergoing chronic antiplatelet therapy. Methods The study was conducted through retrospective examination of the medical records of 153 patients using chronic antiplatelet therapy and those qualified for tooth extraction. The largest group comprised 74 patients using aspirin and clopidogrel as dual platelet antiaggregation therapy; in this group 75 tooth extractions were carried out. In all of the patients TachoSil fibrin-collagen patches and stiches were applied to the wounds resulting from tooth removal. Results Following tooth extraction, primary bleeding was stopped in all the patients and their wounds closed via coagulation within 20-30 min. In eight cases, accounting for 4.9% of the patients, secondary bleeding occurred and was successfully stopped only by applying a pressure dressing soaked in tranexamic acid. Secondary bleeding occurred in three patients on the second day and in five patients on the third day following tooth removal. Conclusion Topical application of TachoSil patches following tooth removal in patients using single or dual antiplatelet therapy effectively stopped bleeding and prevented secondary bleeding after tooth extraction.